Bridging the climate gap: A unified framework for crop and livestock information services in Senegal - Ouedraogo, Issa; Siagbe, Golli; Diouf, Latyr; Fatimata, Kone Fatimata (2024)
Climate change is intensifying challenges for agriculture and livestock farming in Senegal, affecting fodder availability, soil fertility, and rural food security. Climate Information Services (CIS) play a critical role in supporting farmers and transhumant livestock keepers. Stakeholders like ANACIM, Multidisciplinary Working Groups (MWGs), private startups, and NGOs disseminate meteorological data and agro-climatic advice via SMS, community radios, and digital platforms. However, CIS effectiveness is hindered by fragmented coordination, insufficient funding, and the lack of a unified dissemination framework. Establishing a harmonized national system, enhancing MWGs, fostering institutional partnerships, and ensuring year-round information dissemination for pastoralists are vital steps to address these gaps. Strengthened collaborative approaches will improve resilience in agriculture and livestock sectors, bolstering food security and economic stability for rural communities.